Chiococca plowmanii, a new species endemic to the coastal vegetation of northeastern Brazil, and a realignment of Chiococca nitida (Rubiaceae) - Delprete, Piero G. (Revista de Biologia Neotropical / Journal of Neotropical Biology, 2017)
Ver resumo em pdf no artigo.